Theoretical approach to the factors of the crime of sexual assault - hamza_, ahlem (Journal of Social Sciences and Humanities, 2025)
The aim of these study ills to identify the psychological and the social factors that to the crime of sexual assault in Algeria. Since we can't deity these factors or reject ill, because il is not limited only on the criminal but also on the society and the victim, and this form analytical of these theories explaining the commission of the crime referring to previous studies which exanimated the factories and causes that lead to the commission of sexual crimes un Algeria